ATIM-29. IDENTIFYING IMMUNOLOGICAL BARRIERS TO IMMUNOTHERAPY IN PATIENTS WITH GLIOBLASTOMA MULTIFORME. (11th November 2019) - Gustafson, Michael; Parney, Ian; Dietz, Allan
Abstract: Recent successes in cancer immunotherapy have provided new avenues for the treatment of glioblastoma multiforme (GBM). Several immunotherapeutic approaches are now being utilized to treat patients with GBM including checkpoint inhibition, autologous/CAR-T cell therapy, and cancer vaccines. Preliminary data suggests that the majority of patients have sub-optimal clinical responses to these therapies. The impaired anti-tumor immune responses observed in these patients are likely a consequence of immune system dysfunction contributed to by a variety of factors that include diminished antigen presentation/detection, leukopenia, alterations in cytokine levels and cellular mediators. We have previously demonstrated that patients with GBM exhibit profound immune suppression resulting from both tumor and treatment related effects via a comprehensive quantitation of peripheral blood leukocytes by flow cytometry. We hypothesize that the depth and breadth of immunosuppression will significantly affect responses to immunotherapy. Prominent phenotypic abnormalities observed in GBM patients include elevated levels of CD14 + HLA-DR lo/neg monocytes and reduced absolute CD4 T cell counts. We will present data how these and other phenotypes may potentially influence responses to patients treated with dendritic cell vaccines. Our goal is to understand the role of these cells in the context of immunosuppression not only to facilitate the development of targeted immunotherapies to circumvent their effects, but also to potentially utilize them as biomarkers for understanding diverse responses to immunotherapies.